Enhanced electrochemical conductivity of surface-coated gold nanoparticles/copper nanowires onto screen-printed gold electrode - Kusnin, Norzila; Yusof, Nor Azah; Ab Mutalib, Nurul Asyikeen; Mohammad, Faruq; Abdullah, Jaafar; Sabri, Suriana; Mustafa, Shuhaimi; Mohamad Saman, Ahmad Farabi; Mohd Faudzi, Fatin Nabilah; Soleiman, Ahmed A. (Multidisciplinary Digital Publishing Institute, 2022)
Electrochemical application has been widely used in the study of biosensors. Small biomolecules need a sensitive sensor, as the transducer that can relay the signal produced by biomolecule interactions. Therefore, we are improvising a sensor electrode to enhance electrochemical conductivity for the detection of small DNA molecule interaction. This work describes the enhanced electrochemical conductivity studies of copper nanowires/gold nanoparticles (CuNWs/AuNPs), using the screen-printed gold electrode (SPGE). The AuNPs were synthesized using the Turkevich method as well as characterized by the high-resolution transmission electron microscopy (HRTEM) and ultraviolet-visible (UV-Vis) analysis for the particle size and absorption nature, respectively. Further, the surface morphology and elemental analysis of a series of combinations of different ratios of CuNWs-AuNPs-modified SPGE were analyzed by field emission scanning electron microscopy (FESEM) combined with an energy dispersive X-ray (EDX). The results indicate that the nanocomposites of CuNWs-AuNPs have been randomly distributed and compacted on the surface of SPGE, with AuNPs filling the pores of CuNWs, thereby enhancing its electrochemical conductivity. The cyclic voltammetry (CV) method was used for the evaluation of SPGE performance, while the characterization of the electrochemical conductivity of the electrode modified with various concentrations of AuNPs, CuNWs, and different volumes of dithiopropionic acid (DTPA) has been conducted. Of the various parameters tested, the SPGE modified with a mixture of 5 mg/mL CuNWs and 0.25 mM AuNPs exhibited an efficient electrochemical conductivity of 20.3 µA. The effective surface area for the CuNWs-AuNPs-modified SPGE was enhanced by 2.3-fold compared with the unmodified SPGE, thereby conforming the presence of a large active biomolecule interaction area and enhanced electrochemical activity on the electrode surface, thus make it promising for biosensor application.